2009
DOI: 10.1016/j.humpath.2008.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and phenotypic analysis of poorly differentiated sinonasal neoplasms: an integrated approach for early diagnosis and classification

Abstract: Accurate early diagnosis of poorly differentiated tumors of the sinonasal and skull-base sites is critical to modern multimodality management of patients with these tumors. A combined phenotypic and sequential biomarkers approach of a large retrospective cohort of these tumors led to the reclassification of some cases and the confirmation of uncertain diagnoses in others. An integrated algorithm of selected markers and phenotypic features for biopsy-based diagnosis of these tumors is presented and discussed. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 38 publications
(41 reference statements)
3
25
0
1
Order By: Relevance
“…A total of 49 cases of proposed sinonasal EFT have been reported in the English language literature thus far [3,8,13,15,, 11 of which were confirmed with molecular studies [15,17,19,26,[37][38][39] and 21 of which have reported follow-up or outcomes [8, 13, 15, 19, 20, 22-26, 33, 35-37, 39, 40]. The pertinent information on previous cases of EFT with follow-up available is presented in Table 3.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…A total of 49 cases of proposed sinonasal EFT have been reported in the English language literature thus far [3,8,13,15,, 11 of which were confirmed with molecular studies [15,17,19,26,[37][38][39] and 21 of which have reported follow-up or outcomes [8, 13, 15, 19, 20, 22-26, 33, 35-37, 39, 40]. The pertinent information on previous cases of EFT with follow-up available is presented in Table 3.…”
Section: Discussionmentioning
confidence: 69%
“…The cases in this study were all considered diagnostic without molecular confirmation, although FISH or RT-PCR, was performed in 8 cases and shown to be positive. A recent study by Cordes et al demonstrated a EWSR1-FLI1 fusion transcript by RT-PCR on frozen tissue in only 4 of 10 cases of typical sinonasal EFT [17]. A negative RT-PCR study does not rule out alternative fusion gene partners for EWSR1, present in as much as 15% of EFT cases in other locations [1].…”
Section: Discussionmentioning
confidence: 99%
“…Occasional cases may show neuroendocrine markers (such as chromogranin, synaptophysin, CD56 or CD57), but reactivity is usually weak and limited. Pituitary hormone and transcription factors are negative [63][64][65][66]. Again, the management with multimodality therapy is very different from the management for ESSPA, with a very different prognosis and outcome.…”
Section: Differential Diagnosismentioning
confidence: 99%
“…38,39 Outcome and management. Rhabdomyosarcoma is considered a systemic disease, managed with multimodality therapies including surgery, chemotherapy and radiation, 40 frequently associated with adverse late sequela of treatment. 41 There is an overall poor prognosis of sinonasal tract alveolar rhabdomyosarcoma (5-year survival 30-40%), 29,35,[41][42][43][44] with patients frequently showing regional and/or distant metastases, although young patients (5-year survival 62.5%) tend to have a better prognosis.…”
Section: Mesenchymal Chondrosarcomamentioning
confidence: 99%